2021
DOI: 10.1007/s40726-021-00189-1
|View full text |Cite
|
Sign up to set email alerts
|

Virus Disinfection and Population Genetics: Toward the Control of Waterborne Virus Diseases by Water Engineering

Abstract: Purpose of Review Major waterborne viruses comprise numerous variants rather than only a master sequence and form a genetically diverse population. High genetic diversity is advantageous for adaptation to environmental changes because the highly diverse population likely includes variants resistant to an adverse effect. Disinfection is a broadly employed tool to inactivate pathogens, but due to virus evolvability, waterborne viruses may not be inactivated sufficiently in currently applied disinfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 64 publications
3
6
0
Order By: Relevance
“…Our free chlorine disinfection experiments showed a surprising result; the substitution of Met by aliphatic ones did not coincide with a lowered sensitivity to free chlorine. This finding contradicts hypotheses raised by prior studies on the role of oxidizable residues in free chlorine disinfection, ,,,, but is consistent with reports on the absence of chlorine resistance in PV1 following a Met to Val substitution in VP1 . The sensitivity to other oxidants, such as peracetic acid are also believed to be governed by the structure and protein compositions of viruses. , Our result with free chlorine implies a need to revisit this hypothesis.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our free chlorine disinfection experiments showed a surprising result; the substitution of Met by aliphatic ones did not coincide with a lowered sensitivity to free chlorine. This finding contradicts hypotheses raised by prior studies on the role of oxidizable residues in free chlorine disinfection, ,,,, but is consistent with reports on the absence of chlorine resistance in PV1 following a Met to Val substitution in VP1 . The sensitivity to other oxidants, such as peracetic acid are also believed to be governed by the structure and protein compositions of viruses. , Our result with free chlorine implies a need to revisit this hypothesis.…”
Section: Discussionsupporting
confidence: 79%
“…Free chlorine has been found to oxidize the viral capsid, , which protects the viral genome from chemical and enzymatic damage, , and has been reported to inhibit the viral attachment function, thereby partially contributing to enterovirus inactivation. ,,, Sulfur-containing amino acids (cysteine (Cys) and methionine (Met)) react with free chlorine much faster than other amino acid residues. , Thus, differing abundances and solvent-accessibilities of Cys and Met in capsid proteins have been suggested as a rationale for the varying virus sensitivities to commonly used oxidants. ,,, This theory is consistent with the findings on the free chlorine susceptibility of 13 environmental isolates of CVB5, where isolates belonging to genogroup B, which contain fewer Met in the capsid proteins, also exhibited a 1.9-fold lower sensitivity to free chlorine compared to isolates falling within genogroup A …”
Section: Introductionmentioning
confidence: 99%
“…Future studies also need to assess cross-resistance with other disinfectants which has been demonstrated previously ( Zhong et al, 2017 ). Kadoya et al (2021) suggests that multiple disinfection processes are effective to prevent viral adaptation to disinfection when disinfection works as a form of natural selection. Because the lime treatment can work as natural selection, it is appropriate to add other disinfection processes in a sanitation system to ensure the safe of human health.…”
Section: Discussionmentioning
confidence: 99%
“…60 Disinfection may be involved in virus evolution because it can work as selection pressure and a bottleneck. 61 The role of disinfection as an evolutionary force and adaptation mechanism is yet to be characterized for disinfection methods commonly applied to excreta matrices, including heat treatment and the use of ammonia and lime. Future studies should investigate how the specific virucidal factors in individual disinfection (e.g., increasing temperature, increasing pH, and ammonia concentration) are involved in virus evolution, which leads to better sanitization strategies in specific resource recovery technologies.…”
Section: ■ Virus Inactivation In Excreta Matricesmentioning
confidence: 99%
“…Previous studies have investigated the adaptation mechanisms or underlying change in a genome sequence of a disinfection-resistant population, for example, murine norovirus to free chlorine and human echovirus 11 to ultraviolet radiation and chlorine dioxide . Disinfection may be involved in virus evolution because it can work as selection pressure and a bottleneck . The role of disinfection as an evolutionary force and adaptation mechanism is yet to be characterized for disinfection methods commonly applied to excreta matrices, including heat treatment and the use of ammonia and lime.…”
Section: Virus Inactivation In Excreta Matricesmentioning
confidence: 99%